Effect of Ca Ion Exchanged to the CO2 Adsorption on HZSM-5 Zeolites - Sang Kompiang Wirawan (ASEAN Journal of Chemical Engineering, 2009)
The adsorption behavior of CO2 on HZSM-5 and CaZSM-5 zeolites was investigated by a step change response method. Temperature programmed desorption (TPD) and in-situ fourier transform infrared (FTIR) spectroscopy were also performed to study the type of adsorbed species and their thermal stabilities. The adsorption experiments were carried out at temperatures from 323 to 473 K and CO2 partial pressures were below atmospheric pressure. The results indicated that CO2 was adsorbed on HZSM-5 by one type of adsorption, and on CaZSM-5 zeolites by at least two types of adsorption over the temperature range studied. One was a weak adsorption probably due to interaction with the framework of ZSM-5, and the other was a stronger adsorption caused by interactions with the Ca cations of ZSM-5. The adsorption behavior for HZSM-5 was adequately described by a single site Langmuir adsorption model but for CaZSM-5 a dual site Langmuir model was required. FTIR-spectra at various elevated desorption temperatures after adsorption of CO2 at low temperature revealed that CO2 was adsorbed on HZSM-5 and CaZSM-5 in several ways and formed carbonate bands, which seemed to be caused by different adsorption sites. The maximum temperatures at which carbonate species were observed were 573 K for HZSM-5 and 673 K for CaZSM-5. The TPD results indicated that the quantity of irreversibly adsorbed CO2 on HZSM-5 was undetectable.